Cutting tool with TiAlN coating

By using CVD-deposited aluminum-titanium nitrogen coating on metal cutting inserts and adjusting their residual stress differences, the residual stress problem after coating at high temperatures is solved, improving the debris resistance and wear resistance of the blades, and extending the tool life.

CN119654439APending Publication Date: 2025-03-18ISCAR LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380058381.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-10
Filing Date
2023-07-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

After the existing metal cutting insert is coated at high temperature, residual stress is easily formed, affecting its wear resistance and adhesion, resulting in a shortening of the tool life.

Method used

At least one coating containing aluminum, titanium and nitrogen is formed on the substrate of the metal cutting insert by chemical vapor deposition (CVD) method, with a specific component of (AlxTi1-xMy)CzN1-z. By adjusting the residual stress difference|S1-S2| of the coating between 10 and 500 MPa, the mechanical properties of the fore and backplane surface are optimized.

Benefits of technology

The debris resistance, wear resistance and tool life of metal cutting inserts is significantly improved, especially when milling steel or cast iron materials, extending the tool life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654439A_ABST
    Figure CN119654439A_ABST
Patent Text Reader

Abstract

A metal cutting insert has a cemented carbide, cermet or ceramic substrate body and at least one cutting edge defined between a rake face and a flank face. The cutting insert has a CVD coating comprising a layer of aluminum titanium nitride having an areal centripetal lattice structure represented by the formula (AlxTi1-xMy) CzN1-z wherein the stoichiometric coefficient of aluminum is 0.30 lt; xlt; 0.95 where M is at least one element selected from Cl and Ar, the stoichiometric coefficient of which is 0 lt; yt; Yt; 0.01, and wherein the stoichiometric coefficient of carbon is 0 < = zlt; and 0.3. The (AlxTi1-xMy) CzN1-z layer satisfies the relationship 10 lt; s1 to S2lt; 500 MPa, where S1 is the residual stress measured on the rake face and S2 is the residual stress measured on the flank face.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a metal cutting insert coated with at least one layer comprising aluminum, titanium and nitrogen applied by chemical vapor deposition. The layer has different residual stresses on the rake face and the flank face of up to 500 MPa, and a method for producing the layer. The invention also relates to a system for metal cutting, comprising an insert holder and at least one such metal cutting insert. Background Art

[0002] Metal cutting tools, in particular cutting inserts, have a hard substrate of cemented carbide, cermet, ceramic or steel and are usually coated with a hard material coating that improves wear or cutting properties. Known coatings for metal cutting tools include carbides, nitrides, oxides, carbonitrides, oxynitrides, oxycarbides, oxycarbonitrides, borides, boron nitrides, boron carbides, boron carbonitrides, boron oxynitrides, boron oxycarbides or boron oxycarbonitrides, layers of mixed metal phases and phase mixtures of the above compounds of elements of groups IVa to VIIa of the periodic table and / or aluminum. Examples of the above compounds are Al2O3 and titanium-based coatings such as TiN, TiC, TiCN and TiAlN. These coatings are applied by CVD methods (chemical vapor deposition), MT-CVD methods (medium temperature chemical vapor deposition), PCVD methods (plasma-supported CVD methods) or by PVD methods (physical vapor deposition). Coatings containing titanium and nitrogen generally have lower oxidation temperatures than coatings containing titanium, nitrogen and aluminum, because the latter group of coatings forms a thin surface layer of aluminum oxide during hot, dry machining applications. Higher aluminum content further increases hardness.

[0003] The CVD deposition method of cubic titanium aluminum nitride coatings (TiAlN) is well known and is described, for example, in Czettl, Christoph & Schleinkofer, U & Schedle, F & Wolf, C & Lechleitner, M & Holzschuh, Helga & Bürgin, W. (2017). CVD TiAlN-Development and challenges for use in mass production History and development of CVD-TiAlN, 19th Plansee Seminar, June 2017. One of the advantages of cubic face-centered TiAlN deposited by CVD compared to TiAlN deposited by PVD is that the TiAlN layer deposited by CVD can have a thickness greater than that of the TiAlN layer deposited by PVD, thus increasing the tool life. Another advantage is that the aluminum content of the cubic CVD TiAlN can be higher than the aluminum content of the cubic PVD TiAlN layer, i.e., more than 60% or 70% of the metal content of the coating, which gives the high-aluminum CVD TiAlN layer superior oxidation resistance. Some CVD TiAlN coatings may have a preferred orientation or structure.

[0004] After coating at high temperatures, residual stresses may form, for example between the coating and the substrate and / or between the layers of the coating, due to the different thermal expansion coefficients of the different materials in the coating and the substrate. Although there are CVD processes that result in coatings with compressive residual stresses, generally, CVD coatings exhibit tensile residual stresses after deposition. Residual stresses are known to affect the wear resistance of metal cutting inserts and the adhesion of their coatings to their substrates.

[0005] Residual stresses are usually determined by non-destructive and phase-selective X-ray diffraction methods such as sin 2 The residual stress is measured in the Ψ method, the Universal Plot method or the Single Tilt method. It is known to those skilled in the art that repeated residual stress measurements at the same location on a sample will not give the same measurement, but will be within a standard deviation within which it will be considered to have the same residual stress (see, for example, He, Baoping Bob and Kingsley L. Smith. "Strain and Stress Measurements with a Two-Dimensional Detector." (1999)). Sometimes the geometry of the cutting insert complicates the measurement of residual stress, but there are known methods to overcome this problem.

[0006] Post-coating mechanical surface treatments that regulate residual stresses in cutting tool coatings are generally advantageous because surface cracks are thereby prevented or closed, and the fatigue properties of the coating are improved, and the life of the cutting insert is extended. It is known that these post-coating treatments (including, for example, sandblasting, shot peening or brushing of cutting inserts coated with CVD layers, PCVD layers or PVD layers) reduce the tensile residual stress of one or more outer layers of the coating or the entire coating or even the substrate or increase its compressive residual stress. However, compressive stresses exceeding a certain point may lead to adhesion problems and spontaneous breakage, chipping or separation of the surface coating. Post-coating treatments are also used to change the surface roughness, or at least partially remove the uppermost layer on the front and / or rear face and / or cutting portion, and / or increase the hardness of the coating. Residual stress is typically measured in megapascals (MPa), where tensile residual stress has a positive sign "+" and compressive residual stress has a negative sign "-".

[0007] Examples of various and somewhat contradictory disclosed desired residual stress ranges for CVD TiAlN layers in coatings for cutting inserts include, for example, residual stresses between 300 MPa and -5000 MPa within 500 μm of the cutting edge, or between -0.4 GPa and -0.3 GPa, or between -0.5 GPa and -5 GPa, and a formula giving the difference between the maximum and minimum values ​​of the residual stress for any of the rake face, flank or cutting edge as 0.5 GPa to 3 GPa, for example WO 2020 / 079952, or confusingly 3 GPa to 5 GPa.

[0008] One common cause of failure of cutting tools coated with such coatings in applications such as milling or turning is chipping on the rake face and / or cutting edge. Summary of the invention

[0009] It is therefore an object of the present invention to provide a metal cutting insert for machining refractory metals, hard metals and iron-based materials, in particular cast iron and stainless steel. A metal cutting insert according to one aspect of the present invention is coated with a coating comprising at least one layer of aluminum titanium nitride deposited in a chemical vapor deposition (CVD) process, the coated cutting insert having improved toughness, improved chip resistance and longer tool life compared to the prior art, wherein the difference in residual stresses of the rake face and the flank face after blasting of the rake face and / or the flank face has an upper limit. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 : 2D detector setup for the single-tilt method.

[0011] Figure 2a : Tool life of samples A2i and A2ii normalized by tool life of prior art samples B2i and B2ii on two different workpieces, Figure 2b : Comparison of tool life of samples B2i and B2ii.

[0012] Figure 3a : Pictures of the rake face and cutting edge of sample A2i after 28 minutes of milling of a GGG50 workpiece. Figure 3b : Pictures of the rake face and cutting edge of sample A2ii after 32 minutes of milling of a GGG50 workpiece. Figure 3c : Pictures of the rake face and cutting edge of sample B2i after 28 minutes of milling of a GGG50 workpiece. Figure 3d : Pictures of the rake face and cutting edge of sample B2ii after milling a GGG50 workpiece for 28 min.

[0013] Figure 4a : Pictures of the rake face and cutting edge of sample A2iii after milling a SAE4340 workpiece for 1.7m. Figure 4b : Pictures of the rake face and cutting edge of sample A2iv after milling a SAE4340 workpiece for 4.8 m. Figure 4c : Comparison of the rake face and cutting edge of sample B2iii after milling SAE4340 workpiece for 1.7m. Figure 4d : Photos of the rake face and cutting edge of comparison sample B2iv after milling SAE4340 workpiece for 4.8 m.

[0014] Figure 5a : Single XRD 2D frame for residual stress evaluation; Figure 5b : Integrate the frame into a 1D spectrum.

[0015] Figure 6a : Unpolished surface of the blade of a x100 lens of an NHT3 nanoindentation tester manufactured by Anton Paar GmbH; Figure 6b : Polished surface of the blade with a x100 lens of an NHT3 nanoindentation tester manufactured by Anton Paar GmbH, where the X indicates the appropriate location for nanoindentation measurement.

[0016] Figure 7 : The working angle of the blade.

[0017] Figure 8a According to the present invention, as deposited (Al x Ti 1-x M y )C z N 1-z SEM micrograph of the surface showing well-defined cubic grains.

[0018] Figure 8b: After the coating post-treatment, the surface of (Al x Ti 1-x M y )C z N 1-z under the same magnification as the SEM micrograph showing a "smudged" surface. Figure 8a Specific Embodiments

[0019] This object is achieved by a metal cutting insert (hereinafter referred to as "cutting insert") made of a substrate of cemented carbide, cermet or ceramic and a coating formed on the substrate by chemical vapor deposition; the substrate body includes at least one rake face and at least one flank face, the rake face and the flank face intersect to form a cutting edge having at least one working angle as shown in Figure 7 , the coating has one or more layers, wherein at least one layer has a composition containing aluminum, titanium and nitrogen, which has a face-centered cubic lattice structure, represented by the formula (Al x Ti 1-x M y )C z N 1-z , where the stoichiometric coefficient of aluminum is 0.30 < x < 0.95, preferably 0.50 < x < 0.95, more preferably 0.67 < x < 0.95, and advantageously 0.8 < x < 0.90, where M is at least one element selected from Cl and Ar, and the stoichiometric coefficient of M is 0 ≤ y < 0.01, preferably 0 ≤ y < 0.005, and where the stoichiometric coefficient of carbon is 0 ≤ z < 0.3; characterized in that the (Al x Ti 1-x M y )C z N 1-z layer satisfies the relation 10 < |S1 - S2| < 500 MPa, preferably 10 < |S1 - S2| < 400 MPa, most preferably 10 < |S1 - S2| < 350 MPa, where S1 is the residual stress measured on the rake face and S2 is the residual stress measured on the flank face.

[0020] Surprisingly, it was found that cutting inserts according to the present invention having a coating within these parameters have better wear resistance, in particular chip resistance, than known cutting inserts and therefore have a longer tool life (for example when mounted on an insert holder and used in a metal cutting method), in particular when milling steel or cast iron materials and turning iron-based workpieces, than known cutting inserts, the tool life of which may be shortened due to flank wear or pitting wear and / or chipping at the cutting edge, in particular in milling due to thermal fatigue from thermal cyclic loads, which leads to stress cracks along the cutting edge, which penetrate completely through the coating, ultimately causing partial pullout of the carbide and ultimately as chipping.

[0021] In particular, CVD (Al x Ti 1-x M y )C z N 1-z (Preferably high aluminum (Al x Ti 1-x M y )C z N 1-z The combination of adjusting the residual stress in the cutting edge layer, S1 and S2 on the rake face and flank face of the working angle to their respective defined ranges as discussed below, and adjusting the residual stress difference |S1-S2| to less than 500MPa gives the cutting insert increased chip resistance, improved wear resistance and significantly longer tool life.

[0022] The residual stress S1 is preferably in the range of |S1| < 3100 MPa. In some embodiments, the residual stress S1 is in the range of |S1| < 2800 MPa, while in other embodiments, -2200 ≤ S1 < 2400 MPa.

[0023] If the residual stress of S1 exceeds 3100 MPa, the tool life is reduced. The inventors have found that the wear resistance of the cutting tool is improved over the entire range of S1 described above. Compressive stress leads to an increase in tool life, however too high a compressive stress may cause spalling.

[0024] The residual stress S2 is preferably in the range of |S2|<2800MPa. In some embodiments, the residual stress S2 is in the range of |S2|<2500MPa, while in other embodiments, -1700≤S2<1900MPa. The inventors have found that within the range of S2, the wear resistance of the cutting tool is improved by reducing chipping and improved toughness.

[0025] (Al x Ti 1-x M y )C z N1-z The thickness of the layer may be between 2 and 15 μm, preferably between 3 and 15 μm, most preferably between 4 and 10 μm. The thickness of the coating may be between 2 and 25 μm, preferably between 3 and 20 μm, most preferably between 4 and 15 μm.

[0026] Tensile stresses usually occur in CVD coatings due to the difference between the thermal expansion coefficients of the substrate and the coating. Generally, it is desirable to reduce the tensile residual stresses or to introduce compressive residual stresses in the coating (usually on the rake face and / or on the cutting edge), since surface cracks are thereby prevented or closed, and this improves the fatigue properties of the coating and thereby the fatigue properties of the tool. The adjustment of the residual stresses is obtained by post-coating treatments (e.g. brushing, sandblasting, shot peening, etc.).

[0027] The surface integrity of the outermost layer is altered by post-coating treatments that induce plastic deformation of the surface layer, i.e., the surface morphology is changed. This deformation is discernible under a microscope, e.g. Figure 8a and Figure 8b The differences between are shown. Figure 8a The outermost deposition state (Al x Ti 1-x M y )C z N 1-z The as-deposited morphology of the layer shows polyhedral grains with well-defined faces and vertices. In contrast, the morphology of the surface after post-treatment, such as coating, Figure 8b The "smeared" topographic surface of the sandblasting according to some embodiments of the present invention is shown, which shows the outermost (Al x Ti 1-x M y )C z N 1-z Plastic deformation of a layer in which at least some of the uppermost vertices of the polyhedral grains undergo deformation over a large area of ​​the micrograph. The term "outermost" is synonymous with "uppermost" and is relative to the substrate, ie farthest from the substrate.

[0028] In some embodiments, at least one rake face or side face has undergone post-coating treatment resulting in a surface morphology that appears as smeared in at least 90% of the area of ​​the micrographs. Other embodiments have at least one rake face or side face that appears as smeared in at least 70% of the micrographs or appears as smeared in at least 50% of the micrographs, or in some embodiments, after very slight post-coating treatment, at least one rake face or side face has undergone post-coating treatment resulting in a surface morphology that appears as smeared in at least 20% of the area of ​​the micrographs.

[0029] Typically, post-coating treatment is continued until residual compressive stress is achieved. Compressive stress generally results in better wear resistance, especially for adhesive wear at high temperatures, however too high a compressive stress may result in cohesive and / or cohesive peeling, adhesion problems and chipping of the coating.

[0030] Without being bound by any theory, the adjustment of the residual stress difference between the rake face and the flank face after the coating post-treatment to improve fatigue properties is believed to reduce the residual stress at the cutting edge (Al x Ti 1-x M y )C z N 1-z The titanium aluminum nitride coating was found to exhibit unique behavior because the flank and / or rake face should be treated so that the (Al2O3) x Ti 1-x M y )C z N 1-z The strain induced in the layer is within the range defined in claim 1, otherwise the uneven mechanical properties at the cutting edge will adversely affect the tool life. Preferably, the (Al x Ti 1-x M y )C z N 1-z The residual stress in the layer reduces the tensile residual stress, or introduces (Al x Ti 1-x M y )C z N 1-z The compressive residual stress in the layer is within the specific range of S1 and S2 mentioned above. Preferably, the (Al x Ti 1-x M y )C z N 1-z The Vickers hardness in the layer is within the range defined in claim 10 .

[0031] The substrate of the cutting insert can be a shape commonly used for cutting inserts, for example, the top view of the cutting insert can be a square, a rhombus, a triangle, a circle, an ellipse, etc. Preferably, the cutting insert should be a milling cutting insert. The substrate includes at least one flank face and at least one rake face. The flank face (also referred to as the side) and the rake face are connected to each other by a cutting edge line. For example, expressions such as "flank face", "rake face", "cutting edge", etc. include the surface of the substrate and the coating thereon in their meaning.

[0032] (Al x Ti 1-x My )C z N 1-z The layer may have at most 15 vol% of the hexagonal phase. If the proportion of the (Al x Ti 1-x M y )C z N 1-z phase is too high, the wear resistance is reduced and the tool life is shortened. An even higher proportion of the (Al x Ti 1-x M y )C z N 1-z fcc phase is beneficial to improving the wear resistance. A preferred embodiment has at most 5 vol% of the hexagonal phase and most preferably about 100 vol% of the fcc phase.

[0033] (Al x Ti 1-x M y )C z N 1-z The layer may include one or more features of known aluminum-rich titanium aluminum nitride or titanium aluminum carbonitride deposited by CVD methods known in the art, for example, by way of example, a columnar crystal structure with an aspect ratio of, for example, about 2.5 to 7, a layered structure with periodically alternating regions having alternating different stoichiometric ratios of Ti and Al, where the stoichiometric ratio of the entire layer is 0.5 < x < 0.95, and / or the precipitation at the grain boundaries has a higher Al content than within the grains.

[0034] The CVD coating of the present invention can be manufactured by known methods in an industrial-scale thermal CVD reactor as described in JP 2001 / 341008. Alternatively, the CVD coating can be manufactured by the method described by S. Anderbouhr et al. in the Proceedings of the 14 th International Conference of 1997. Another known thermal CVD method that can be used for depositing a Ti 1-x Al x N layer on a cemented carbide substrate is described in EP1902155. Another known thermal CVD method for depositing a Ti 1-x Al x N layer on a cemented carbide substrate in a hot-wall low-pressure CVD apparatus is described in "Aluminium-rich Ti 1-x Al x N Coatings by CVD" - EuroPM2006 - Hard Materials Thin and Thick Coatings.

[0035] Some more examples of known CVD methods for producing aluminum-rich cubic titanium aluminum nitride or titanium aluminum carbonitride layers are disclosed in US6040012, Surface & Coatings Technology 205 (2010) 1307-1312, WO 2020 / 079952, US9976213, EP 3441167 and US 2018 / 0216224.

[0036] Trace elements of chlorine and / or argon that may be in the coating come from the gases used in the CVD process, such as, for example, TiCl4, AlCl3 and, optionally, Ar as a carrier gas. These trace elements may be present in the layer in amounts up to 1 atomic %, but exceeding 1 atomic % is detrimental and reduces the hardness of the layer. In some embodiments, (AlCl3) may be present in the layer in amounts up to 1 atomic %. x Ti 1-x M y )C z N 1-z The layer has no trace elements, ie, y=0, and the layer has improved mechanical properties. In some embodiments, z=0, ie, the layer is (Al x Ti 1-x M y )N or (Al x Ti 1-x )N.

[0037] The cutting insert substrate can be any substrate known for cutting inserts. In a preferred embodiment, the substrate is made of a hard metal (also referred to as cemented carbide), which is made of tungsten carbide and cobalt and optionally carbides, nitrides or carbonitrides of elements of groups IVa to VIIa of the periodic table. In some embodiments, the cemented carbide substrate can have no β-zone, which improves the toughness of the substrate body and is particularly used for machining steel, while other embodiments, such as, for example, machining cast iron, do not have no β-zone. In other embodiments, the substrate can be a cermet, high speed steel, ceramic, cubic boron nitride sintered substrate and silicon nitride sintered substrate. The substrate of the cutting insert can be a cemented carbide, for example, it has a composition of 90.5 mass % WC, 0.5 mass % Cr3C2, 9 mass % Co, which is sintered into a cutting tool geometry.

[0038] In some embodiments, the rake face may be a flat surface, while some embodiments may have additional features such as, for example, a chip breaker. Similarly, this also applies to the flank face, which may be chamfered, formed as an uneven surface.

[0039] In some embodiments, the coating consists of a single layer (Al xTi 1-x M y )C z N 1-z In other embodiments, the coating may have one or more additional layers. The one or more additional layers may have carbides, nitrides, oxides, carbonitrides, oxynitrides, oxycarbides, oxycarbonitrides, borides, boron nitrides, boron carbides, boron carbonitrides, boron oxynitrides, boron oxynitrides, boron oxycarbides or boron oxycarbonitrides, mixed metal phases and phase mixtures of the above compounds of elements of Groups IVa to VIIa of the periodic table and / or aluminum. Preferred additional layers include carbides, nitrides or carbonitrides of titanium. In some embodiments, the coating does not include an aluminum oxide layer.

[0040] In a preferred embodiment, the coating is formed between the substrate and (Al x Ti 1-x M y )C z N 1-z There is a TiN bottom layer between the layers, and the substrate is a cemented carbide. In other embodiments, the bottom layer has a TiN layer and a TiCN layer.

[0041] In some embodiments, (Al x Ti 1-x M y )C z N 1-z The layer is the outermost layer of the coating. In these embodiments, (Al x Ti 1-x M y )C z N 1-z At least some of the uppermost vertices of the polyhedral grains of the layer have undergone deformation and appear smeared. In other embodiments, the coating further comprises an outermost layer of TiN. The outermost TiN layer has the advantage of being a wear indicator and / or an easily detectable grade mark. In some embodiments, the outermost layer of the coating comprises a layer selected from TiCN, ZrN and ZrCN, or a multilayer made of layers selected from TiN, TiCN, ZrN and ZrCN. In (Al x Ti 1-x M y )C z N 1-z In embodiments having an outermost layer on the layer, the outermost layer will have a "smeared" topographical surface that exhibits plastic deformation on at least one of the rake face or the side surface of the metal cutting insert.

[0042] In a preferred embodiment, (Al x Ti 1-x M y )C z N1-z The Vickers hardness of the layer satisfies the relation |HV1 - HV2| < 500, preferably |HV1 - HV2| < 300, and most preferably 0 < |HV1 - HV2| < 100, where HV1 is the Vickers hardness measured on the rake face and HV2 is the Vickers hardness measured on the flank face. The Vickers hardness measured on the rake face can be in the range of 2300 < HV1 < 4200, preferably 2600 ≤ HV1 < 3800, more preferably 2900 ≤ HV1 < 3400, and the Vickers hardness measured on the flank face can be in the range of 2400 ≤ HV2 < 4000, preferably 2700 ≤ HV2 < 3600, more preferably 3000 ≤ HV2 < 3500. According to this embodiment, CVD (Al x Ti 1-x M y )C z N 1-z layer (preferably a high-aluminum CVD (Al x Ti 1-x M y )C z N 1-z layer), the residual stress, S1 and S2 on the rake face and the flank face are respectively adjusted to their defined corresponding ranges, and the combination of the adjustment of the residual stress difference |S1 - S2|, together with the adjustment of the Vickers hardness range of HV1, the Vickers hardness range of HV2, and the Vickers hardness range of |HV1 - HV2|, enables the cutting insert to have improved chipping resistance, improved wear resistance, and a significantly longer tool life compared to known cutting inserts, especially in the milling and turning of ferrous workpieces. The tool life of known cutting inserts may be shortened due to flank wear and / or chipping at the cutting edge, especially in milling inserts, and due to thermal fatigue caused by thermal cycling loads, which results in thermal cracks along the cutting edge that completely penetrate the coating, ultimately causing partial pull-out of carbides and ultimately chipping.

[0043] The furnace can be any CVD furnace, for example, by way of example, a Bernex reactor of the BBXpro model or the 750L750S 530L 530S 325L325S models. In some embodiments, the chemical vapor deposition method is enhanced with plasma activation.

[0044] In another aspect of the present invention, there is a method for post-treating a coated cutting insert according to the present invention after depositing a CVD coating on a substrate, the CVD coating having at least one layer (Al x Ti 1-x M y )C z N 1-z, which has stoichiometric coefficients in atomic percentages, 0.30 < x < 0.95, preferably 0.50 < x < 0.95, more preferably 0.67 ≤ x < 0.95, and advantageously 0.80 < x < 0.90, 0 ≤ y < 0.01, 0 ≤ z < 0.3, and M is at least one element selected from Cl and Ar. The rake face and / or the flank face are subjected to one or more post-coating mechanical treatments, such as sandblasting or brushing, which change the residual stress on the rake face and / or the flank face. The term "sandblasting" will include wet sandblasting, dry sandblasting, jet sandblasting, shot peening. The effect of the post-coating treatment changes the surface integrity through plastic deformation of the surface layer, as explained above. Plastic deformation is achieved through dislocation generation and dislocation movement, and dislocation movement changes mechanical properties, such as the microhardness and residual stress of the (Al x Ti 1-x M y )C z N 1-z layer. The "smudged" appearance of the outermost layer will indicate that the face has undergone a post-coating treatment.

[0045] Those skilled in the art will be familiar with known methods of changing the residual stress of such coatings, which have at least one layer of (Al x Ti 1-x M y )C z N 1-z , for example, by way of example, WO2020079952, which describes a sandblasting method preferably along the cutting edge portion while rotating the cutting tool such that the straight line passing through the center of the rake face and perpendicular to the rake face is used as the axis (e.g., 60 rpm), where alumina particles are held at 45° for 10 seconds at a distance of 50 mm. Another example is EP3441167, which describes a wet sandblasting method of a coating with alumina balls, the coating including a layer of nitride or carbonitride of Al x Ti 1-x , the average particle size of the alumina balls is 50 mm, the density is 10 vol%, from a jetting distance of 10 mm, the jetting pressure is 0.2 MPa, and the jetting time is 10 seconds. Another example of a known sandblasting method is described in US 9976213, and it can be a dry or wet sandblasting treatment for 10 - 600 seconds preferably at a sandblasting angle of 90° at a sandblasting agent pressure of 1 - 10 bar, where the sandblasting pressure has a significantly greater effect on the change of residual stress in the coating during the sandblasting duration.

[0046] It is not possible to disclose a wide range of sweep blasting methods, since the residual stresses generated depend not only on the blasting parameters, but also on the structure and thickness of the entire coating. However, taking into account the structure and thickness of the entire coating and the structure and composition of the substrate and the blasting medium selected for the method, the skilled person will be able to carry out some simple experiments to determine the blasting parameters of the rake face and / or the flank face, in the case of known coating post-treatment, so that the difference between the residual stresses of the rake face and the flank face will not be greater than 500 MPa. The parameters may include the blasting pressure, the blasting duration, the blasting angle, the nozzle diameter, the distance between the nozzle and the rake face and the flank face of the blasted blade, and the movement of the nozzle over the blasted surface. The skilled person can determine the parameters well based on a working knowledge of the standard deviations of the parameters, which usually result in a cumulative standard deviation of the residual stresses even for the same blasting conditions.

[0047] The blasting duration is in the range of 2 to 600 seconds, but can also be limited to the range of 5 to 60 seconds. The blasting angle is the angle between the blasting stream from the nozzle to the blasting surface and the respective blasting surface, and can be between 0° and 90°. Suitable blasting agent pressures are in the region of 0.5-10 bar, preferably 1-4.5 bar.

[0048] The blasting agent or medium can be, for example, metal, glass or ceramic particles, optionally round particles, steel, SiC, Al2O3, glass or ZrO2. The inherent stress conditions according to the present invention can be set with any of the described or other suitable blasting agents. According to the common sense of the present invention, those skilled in the art can select the required medium from the perspective of method, technical equipment or tribology, and can obtain suitable blasting parameters by simple tests. The average particle size of the blasting agent is ideally in the region of 90-400 mesh, preferably 180-320 mesh. The blasting medium is pushed to the surface by compressed air in a dry blasting method or by a pressurized fluid in a wet blasting method.

[0049] The blasting angle, i.e. the angle between the treatment beam and the tool surface, has a significant effect on the reduction of tensile residual stresses or the introduction of compressive residual stresses. The largest change in residual stress occurs at a blasting angle of 90°.

[0050] By way of example, a residual stress difference between the rake face and the flank face according to claim 1 can be obtained by blasting both faces at 45° with the same medium for slightly different amounts of time and / or slightly different pressures. An alternative blasting method can be blasting both faces at the rake face / flank face for the same amount of time and / or the same pressure but at different blasting angles, such as, for example, 60° / 30° or 90° / 45°. An alternative blasting method can be blasting only one face, with a short blasting time and / or a low blasting pressure, as long as the residual stress difference is less than 500 MPa. However, the present invention is not limited to these and the blasting methods mentioned below.

[0051] After sandblasting, (Al x Ti 1-x M y )C z N 1-z The layer satisfies the relationship 10<|S1-S2|<500MPa, preferably 10<|S1-S2|<400MPa, most preferably 10<|S1-S2|<350MPa, where S1 is the residual stress measured on the rake face and S2 is the residual stress measured on the flank face. The residual stress S1 may advantageously be in the range of |S1|<3100MPa, preferably |S1|<2800MPa, more preferably -2200≤S1<2400MPa. The residual stress S2 may advantageously be in the region of |S2|<2800MPa, preferably |S2|<2500MPa, and most preferably -1700≤S2<1900MPa.

[0052] Residual stresses are usually measured by non-destructive and phase-selective X-ray diffraction methods. A common method is to use a sin / line detector. 2 Ψ method. When measuring the cubic (Al x Ti 1-x M y )C z N 1-z The relatively low angle at which the (200) reflection occurs when measuring residual stress may make this method difficult to use because the high 2θ peak may not be available or suitable for thin films and coatings.

[0053] The residual stress measurement method used by the inventors is a single tilt method using a 2D detector (see US10,416,102 and Materials Research Proceedings Vol. 6 (2018) pp. 3-8). This method performs X-ray diffraction stress analysis of a sample (such as a film or coating). The sample has a surface having two perpendicular axes S1 and S2 in the plane of the surface, and a third axis S3 perpendicular to the sample surface plane. The X-ray beam is directed to the sample surface at a relatively low angle with respect to the surface plane. X-ray energy is diffracted from the sample and detected with a two-dimensional X-ray detector at multiple rotational orientations of the sample around S3. During the entire X-ray diffraction stress analysis, the third axis S3 is maintained at a constant tilt angle, thereby avoiding significant errors associated with the movement of the cradle track of the goniometer used for X-ray diffraction stress analysis, and measurements at low 2θ angles are highly sensitive to it.

[0054] The measured stress is cubic (Al x Ti 1-x M y )C z N 1-z The stress on the (200) plane. Figure 7 As shown, the stress measurements for S1 and S2 are taken from the same working angle, indicated by the circles. The diffraction vectors of the low 2θ diffraction rings overlap to allow stress tensor measurements at a single tilt angle. Before taking stress measurements, a calibration of the setup is performed (see Figure 1 ). The ψ tilt for stress measurement was chosen to be 40°.

[0055] The surface detector is a BRUKER VANTEC-500 with a diameter of 140 mm. The detector is mounted at a distance of 200 mm from the center of the goniometer, i.e. the center of the detector is 200 mm from the center of the goniometer. The possible area for locating the center of the goniometer is given by Figure 7 Indicated by the arrow in . A Ni filter is used on the first side, followed by a polycapillary focusing optic and a 1 mm nozzle for point focusing. In order to make adequate measurements with such a setup, the intensity of the 2θ value of the observed maximum of the (200) reflection in the sum count of the 2D frame should be at least 0.023%. When the XRD instrument is calibrated by measuring the stress of the (113) reflection of a stress-free powdered alumina sample, it is considered that the instrument is calibrated when the σ11 and σ22 of the biaxial stress tensor are 0±55 MPa (which is the standard deviation of the residual stress measurement).

[0056] Now it is possible to measure cubic (Al x Ti 1-x M y )C z N 1-zThe biaxial stress state in the (200) plane is calculated using The rotation around the Z axis (angle ) is 0° for the first frame and 315° for the 8th frame, with 45° increments between frames. Frame acquisition is not limited by time, but by the total number of counts, a value set in this work to 10,000,000 counts. The actual summed counts for a frame are typically less than this value, but not less than 95,000,000 counts. The detector and tube are set at an angle of 21.196° to capture the cube somewhere in the middle of the detector (Al x Ti 1-x M y )C z N 1-z The integration for the stress calculation was performed over the γ range from 249° to 292°, while the 2θ range was set to ±1° relative to the observed maximum of the (200) reflection of the first frame (ψ = 40°, ). The 2θ range for stress measurements would be from 43.483° to 45.483°, e.g. Figure 5b As shown. It is then divided into 20 sub-regions with a peak rejection of 20% and a step of 0.1°. The peak evaluation is by the Pearson VII method. The crystallization data used are a Poisson value of 0.238 and a Young's modulus of 330667 [MPa]. The value of |S1-S2| can be calculated as |σ111-σ112| or |σ221-σ222|, where σ111 and σ221 are the σ11 and σ22 values ​​in the biaxial stress tensor of the obtained front face, respectively, and σ112 and σ222 are the σ11 and σ22 values ​​in the biaxial stress tensor of the obtained back face, respectively. The biaxial stress tensor is shown below.

[0057]

[0058] To show how to obtain the intensity of the 2θ value of the observed maximum of the (200) reflection in the summed counts of a 2D frame, Figure 5a Display for cubic (Al x Ti 1-x M y )C z N 1-z A single XRD 2D frame for residual stress evaluation, which has a frame detector total count of 9,475,328 counts and a total frame collection time of 156.98 sec. Figure 5b The display integrates the frame into a 1D spectrum, where the integration is performed over the wedge ( Figure 5aThe wedge includes a 2θ range of 41° to 46° and a gamma value of 249° to 292°. The integrated peak observed maximum is at 2θ = 44.483° with a total intensity of 23.2711 CPS. 23.2711 CPS × 156.98 seconds = 3,653 counts. The intensity of the 2θ value of the observed maximum of the (200) reflection in the summed counts of the 2D frame ( Figure 5a The De-Bye ring DbR) shown in is equal to (3,653 counts / 9,475,328 counts) x 100 = 0.038%, which is greater than 0.023% as defined above.

[0059] The strong (200) reflection at ψ = 40° is important for the cubic (Al x Ti 1-x M y )C z N 1-z has a (111) texture with enough grains spread around the x-axis to complete the dihedral angle between the (111) and (200) planes, and a 40° ψ tilt. We can also note the textural effect from the uneven intensity across the De-Bye ring, see Figure 5a DbR.

[0060] Nanohardness measurements were performed on a NHT3 nanoindentation tester manufactured by Anton Paar GmbH. The Berkovich Diamond Nanoindenter penetrated the sample at a linear loading rate of 120 mN / min, reaching a maximum load of 35 mN. Prior to testing, the sample was treated to make the surface suitable for such a test. Surface roughness greatly affects the penetration process of the nanoindenter. In order to provide a suitable surface quality, the sample was gently hand-polished on a soft fiber pad, rotated at 150 rpm, and immersed in colloidal 50 nm SiO2 for about 60 seconds. Figure 6a shows the sample surface before polishing, while Figure 6b Shown is the same surface after polishing. Figure 6b The X in the figure indicates the appropriate location of the nanoindentation measurement. The Vickers hardness values ​​presented are the average of 20 indentations, performed very close to each other. The Poisson's ratio was set to 0.28.

[0061] Example

[0062] Although the present invention will be described in more detail by way of examples, it should be understood that the present invention is not limited thereto.

[0063] Example 1

[0064] A substrate of cemented carbide is prepared from cemented carbide powder having a composition of 89.5% WC, 10% Co, up to 0.5% of another component (e.g. Cr3C2 or VC), all in mass %, which is sintered into an indexable insert, e.g. CNMG 432M3P, having a rake face and a flank face intersecting to form a cutting edge.

[0065] According to the industrial CVD method, in a standard hot furnace for coating metal cutting tools, the insert is coated with a TiN layer and (Al x Ti 1-x Cl y )N layer. First, a TiN layer with a thickness of 0.3 μm is formed on the surface of the substrate at 900°C using H2 carrier gas, TiCl4 gas and N2 gas. Then a TiAlN layer with a thickness of about 8 μm is formed at a temperature in the range of 700-900°C. The gases used are TiCl4 gas: 0.05-4.0% by volume, AlCl3 gas: 0.03-2.5% by volume, NH3 gas: 0.05-3.0% by volume, and the carrier gases flowing into the reactor at a pressure in the range of 2.7-15.9 KPa are H2 and N2.

[0066] The coated inserts were blasted with SiC from a nozzle with a diameter of 0.8 mm at a corresponding blasting stream angle (with a standard deviation of ±5°), with a distance of 10 mm (±0.3 mm) between the nozzle and the insert. The blasting of the rake and flank faces, i.e. the blasting time, blasting pressure, blasting medium and blasting angle, were selected so as to produce different corresponding residual stresses on the rake and flank faces with a difference of less than 500 MPa. Three examples of blasting parameters are given below.

[0067] Three samples of the metal cutting tool of the present invention with coating post-treatment A were blasted with SiC F180, a commonly used blasting medium, and are listed in Table 1.

[0068] Table 1

[0069]

[0070] Four comparative samples of metal cutting tools were subjected to coating post-treatment B of blasting with SiC F180 and are shown in Table 2.

[0071] Table 2

[0072]

[0073] Example 2

[0074] After the blasting treatment, the residual stress on both the rake face and the flank face was measured using the single tilt method for residual stress evaluation. The surface detector was BRUKER's VANTEC-500, with a diameter of 140 mm. The results are shown in Table 1, and |S1-S2| for treatment B is given in Table 2.

[0075] Nanohardness measurements were performed on a NHT3 nanoindentation tester manufactured by Anton Paar GmbH. The samples were gently hand-polished on a soft fiber pad, spun at 150 rpm, immersed in colloidal 50 nm SiO2 for about 60 seconds, and then penetrated with a Berkovich Diamond at a linear loading rate of 120 mN / min up to a maximum load of 35 mN. The Vickers hardness values ​​presented are the average of 4 samples, each of which is the average of 20 indentations, performed very close to each other. The Poisson's ratio was set to 0.28.

[0076] The results are given in Table 3. Table 4 shows the results of Vickers hardness of Comparative Sample B1.

[0077] Table 3

[0078]

[0079] Table 4

[0080]

[0081] Example 3

[0082] In a CVD reactor, eight LNHT 1306PNTR blades were coated with (Al 0.83 Ti 0.17 Cl 0.004 )N layer. Four blades were subjected to post-coating treatment to obtain |S1-S2| of A2 in Table 1 (i.e., A2i, A2ii, A2iii, and A2iv), while four comparative blades with the same geometry were subjected to post-coating treatment B to obtain |S1-S2| of B2 in Table 2 (i.e., B2i, B2ii, B2iii, and B2iv).

[0083] Samples A2i, A2ii, B2i and B2ii were tested in a dry milling test on workpiece 1 of cast iron grade GGG50, and the rake face and cutting edge after the dry milling test are shown in FIG. Figure 3a-3d All of these are photographs taken with an optical microscope. The machining parameters are Vc = 230m / min, f = 0.2mm / rev, Ap = 4.0mm, A e =27mm, where A e is the cutting width.

[0084] Samples A2iii, A2iv, B2iii and B2iv were tested in a wet grinding test on workpiece 2 of steel grade SAE4340. The rake faces and cutting edges of these samples after the wet grinding test are shown in Figures 1 and 2, respectively. Figure 4a-4d All of these are photographs taken with an optical microscope. The wet grinding test parameters are Vc = 200 m / min, f = 0.16 mm / rev, Ap = 2.0 mm, A e =40mm.

[0085] After normalizing the average lifetime of the comparative samples B2i and B2ii to 100%, Figure 2b Compared to the average tool life of samples B2i and B2ii, the average tool life of samples A2i and A2ii has a very significant increase of 230%, as shown in FIG. Figure 2a shown. Figure 2a and Figure 2b The Y-axis is the average normalized life (%). The rake face and cutting edge of sample A2i are shown after 28 and 32 minutes, respectively. Figure 3a The rake face and cutting edge of sample B2i are shown in Figure 3c Among them Figure 3c Sample B2i in Figure 2 shows very significant debris.

[0086] After normalizing the average lifetime of samples B2iii and B2iv to 100%, relative to Figure 2b The average tool life of samples B2iii and B2iv shown, the average tool life of samples A2iii and A2iv has a significant increase of 385% in tool life in SAE4340 milling, as shown in FIG. Figure 2a After 28 and 32 minutes, the rake face and cutting edge of sample A2iii are shown in Figure 4a The rake face and cutting edge of sample A2iv are shown in Figure 4c There was no damage, but after 28 minutes of milling, Figure 4b Sample B2iii in shows significant debris, and Figure 4d Sample B2iv in shows catastrophic debris.

Claims

1. A metal cutting blade, which comprises a substrate body and a coating, The substrate body is a substrate body of cemented carbide, cermet or ceramic; the substrate body includes at least one rake face and at least one flank face, the rake face and the flank face intersect to form a cutting edge, the coating includes one or more layers, wherein at least one layer has a composition containing aluminum, titanium and nitrogen, which has a face-centered cubic lattice structure, represented by the formula (Al x Ti 1-x M y )C z N 1-z , where the stoichiometric coefficient of aluminum is 0.30 < x < 0.95, preferably 0.50 < x < 0.95, more preferably 0.67 < x < 0.95, even more preferably 0.80 < x < 0.90, where M is at least one element selected from Cl and Ar, and its stoichiometric coefficient is 0 ≤ y < 0.01, preferably 0 ≤ y < 0.005, and where the stoichiometric coefficient of carbon is 0 ≤ z < 0.3; Features The x Ti 1-x M y )C z N 1-z The layer satisfies the relationship 10<|S1-S2|<500 MPa, preferably 10<|S1-S2|<400 MPa, and most preferably 10<|S1-S2|<350, where S1 is the residual stress measured on the rake face and S2 is the residual stress measured on the flank face.

2. The metal cutting blade according to claim 1, wherein |S1| < 3100 MPa, preferably |S1| < 2800 MPa, more preferably -2200 ≤ S1 < 2400 MPa, and wherein |S2| < 2800 MPa, preferably |S2| < 2500 MPa, more preferably -1700 ≤ S2 < 1900 MPa.

3. The metal cutting blade according to claim 1 or 2, wherein y = 0.

4. The metal cutting blade according to any one of claims 1-3, wherein z = 0.

5. The metal cutting blade according to any one of claims 1-4, wherein the chemical vapor deposition method has no plasma activation.

6. The metal cutting blade according to any one of claims 1-5, wherein the coating further comprises one or more additional layers, and the additional layer is a layer of a carbide, nitride, oxide, carbonitride, oxynitride, oxycarbide, oxycarbonitride, boride, boron nitride, boron carbide, boron carbonitride, boron oxynitride, boron oxycarbide or boron oxycarbonitride of an element of groups IVa to VIIa of the periodic table and / or aluminum, a mixed metal phase and a phase mixture of the above compounds.

7. The metal cutting insert according to claim 6, wherein at least one of the additional layers is selected from the group consisting of x Ti 1-x M y )C z N 1-z TiN and TiCN between the layer and the substrate.

8. The metal cutting insert according to any one of claims 1 to 7, wherein the coating is composed of a TiN layer deposited on the substrate and the (Al x Ti 1-x M y )C z N 1-z The substrate is composed of a plurality of layers, and the substrate body is a cemented carbide.

9. The metal cutting blade according to any one of claims 1-8, wherein the thickness of the coating is between 2-25 μm, preferably between 3-20 μm, and most preferably 4-15 μm.

10. The metal cutting blade according to any one of claims 4-9, wherein none of the one or more additional layers is an alumina layer.

11. The metal cutting insert according to any one of claims 1 to 10, further characterized in that The x Ti 1-x M y )C z N 1-z The layer satisfies the relationship |HV1-HV2|<500, preferably |HV1-HV2|<300, most preferably |HV1-HV2|<100, wherein HV1 is the Vickers hardness measured on the rake face, and wherein HV2 is the Vickers hardness measured on the flank face.

12. The metal cutting blade according to claim 11, wherein 2300 < HV1 < 4200, preferably 2600 ≤ HV1 < 3800, and more preferably 2900 ≤ HV1 < 3400, and wherein 2400 ≤ HV2 < 4000, preferably 2700 ≤ HV2 < 3600, and more preferably 3000 ≤ HV2 < 3500.

13. A method for producing a metal cutting blade according to any one of the preceding claims, wherein: Applying a coating with a total thickness of 2 - 25 μM to a substrate body of cemented carbide, cermet or ceramic by CVD method, said coating comprising at least one layer containing aluminum, titanium and nitrogen, which has a face - centered cubic lattice structure and is represented by the formula (Al x Ti 1-x M y )C z N 1-z where the stoichiometric coefficient of aluminum is 0.30 < x < 0.95, preferably 0.50 < x < 0.95, more preferably 0.67 < x < 0.95, even more preferably 0.80 < x < 0.90, where M is at least one element selected from Cl and Ar, and its stoichiometric coefficient is 0 ≤ y < 0.01, preferably 0 ≤ y < 0.005, and where the stoichiometric coefficient of carbon is 0 ≤ z < 0.3, and the thickness of the (Al x Ti 1-x M y )C z N 1-z layer is 2 - 25 μm, and wherein after application of the coating, the metal cutting insert is subjected to a sandblasting treatment, wherein the blasting pressure, blasting duration, blasting medium and / or blasting angle of the sandblasting treatment are selected such that after the sandblasting treatment, the (Al x Ti 1-x M y )C z N 1-z The layer satisfies the relationship 10<|S1-S2|<500 MPa, preferably 10<|S1-S2|<400 MPa, and most preferably 10<|S1-S2|<350 MPa, where S1 is the residual stress measured on the rake face, and where S2 is the residual stress measured on the flank face.

14. A system for metal cutting, which comprises a tool holder and at least one metal cutting blade according to any one of claims 1-13.

15. The system according to claim 14, wherein the at least one metal cutting blade is mounted on the tool holder.

16. The metal cutting blade according to claim 1, wherein at least one of the at least one rake face and the at least one flank face has undergone a coating post-treatment.

17. The metal cutting blade according to claim 1, wherein at least one of the at least one rake face and the at least one flank face has tensile residual stress.

Citation Information

Patent Citations

  • Hard-coated body and method for production thereof

    EP1902155A1

  • Surface-coated cutting tool and method for producing same

    EP3441167A1

  • Titanium nitride-aluminum film coated tool and manufacturing method therefor

    JP2001341008A

  • X-ray diffraction device and method to measure stress with 2D detector and single sample tilt

    US10416102B2

  • TOOL WITH TiAIN COATING

    US20180216224A1